2019
DOI: 10.1111/ics.12540
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory / anti‐oxidant activity of ingredients of sunscreen products? Implications for SPF

Abstract: ObjectiveThe Sun Protection Factor (SPF) of sunscreen products is derived from testing in vivo their ability to prevent erythema (“sunburn”). Recently, certain articles have raised concerns that sunscreen products may actively suppress erythema via anti‐inflammatory / anti‐oxidant (AI/AO) activity. These articles reason that this may result in a higher labelled SPF value than that provided by the efficacy of the UVR filters alone, giving consumers a “false sense of security”. On the other hand, since inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“… 62 Other studies have found that these ingredients do not impact the measured SPF. 63 Ending our reliance on in vivo testing, and instead using laboratory tests that directly measure UV protection, 50 would dissuade manufacturers from adding ingredients solely to boost SPF values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 62 Other studies have found that these ingredients do not impact the measured SPF. 63 Ending our reliance on in vivo testing, and instead using laboratory tests that directly measure UV protection, 50 would dissuade manufacturers from adding ingredients solely to boost SPF values.…”
Section: Discussionmentioning
confidence: 99%
“…62 Other studies have found that these ingredients do not impact the measured SPF. 63 Ending our reliance on in vivo testing, and instead using laboratory tests that directly measure UV protection, 50 In 2007 and again in 2011, the US FDA refused to replace the human test with a measured UV absorption one over concerns that the substrates did not adequately mimic human skin and would not until data demonstrated equivalency. 28 This argument is centered on the false assumption of erythema being the only endpoint of health concern.…”
Section: Re Sultsmentioning
confidence: 99%
“…After sun exposure, there may be activation of acute and chronic inflammatory pathways. In this context, antioxidant and anti-inflammatory substances, without the UV filter properties in sunscreen, can also indirectly provide skin photoprotection [75].…”
Section: Discussionmentioning
confidence: 99%
“…Based on their mode of action, UV filters can be classified as (1) physical (inorganic) filters that reflect and scatter the light and (2) chemical UV filters that absorb the UVR (mainly UVB). The efficiency of UV filters is given by SPF value, indicating their ability to protect the skin against UVR; the higher the SPF, the better the sunburn protection [ 32 ]. While the maximum authorised concentrations of chemical UV filters in sunscreen formulations are usually reported at a range of 5–15% w / w of the formulation, physical UV filters could be added at higher concentrations (up to 25% w / w ) [ 33 , 34 ].…”
Section: Sunscreensmentioning
confidence: 99%